Blended Scrum model for software development organizations. Issue 2 (19th November 2018) - Çetin, Esra; Onay Durdu, Pınar
Abstract: Software organizations have to develop software in a short time, and quickly respond to changing requirements. Recently, organizations have started to implement agile development models to reduce cost and increase productivity and quality. Scrum, one of the most widely used agile methodologies, is often implemented in various ways that depart in an uncontrolled fashion from the original model, resulting in development methods often called "ScrumBut." Some argue that such incomplete implementations violate Scrum's core practices and philosophy, while others propose that all methodologies should be adapted to organization's unique culture and integrated with their best practices. In this research, a Blended Scrum model was proposed to overcome uncontrolled ScrumBut issues while transitioning to Scrum. The study was organized as a case study in which software professionals working in Scrum teams were interviewed. In addition, a questionnaire was conducted with other software professionals to determine how agile methods, specifically Scrum, were used. The interviews and questionnaire revealed various Scrum practical implementations. The Blended Scrum model was developed by integrating original Scrum with practices that were determined by interviews and questionnaire conducted with software professionals with real‐world Scrum experience. Finally, the Blended Scrum model was evaluated by Scrum professionals and received positive feedback. Abstract : Scrum is often implemented in various ways resulting in development methods often called "ScrumBut." A Blended Scrum model was proposed to overcome uncontrolled ScrumBut issues. The model was developed by integrating original Scrum with practices from real‐world experiences gathered from software professionals.